Novel Iron-Chelator DIBI Inhibits Staphylococcus aureus Growth, Suppresses Experimental MRSA Infection in Mice and Enhances the Activities of Diverse Antibiotics in vitro - Parquet, Maria del Carmen; Savage, Kimberley A.; Allan, David S.; Davidson, Ross J.; Holbein, Bruce E. (Frontiers in Microbiology, 2018)
DIBI, a purpose-designed hydroxypyridinone-containing iron-chelating antimicrobial polymer was studied for its anti-staphylococcal activities in vitro in comparison to deferiprone, the chemically related, small molecule hydroxypyridinone chelator. The sensitivities of 18 clinical isolates of Staphylococcus aureus from human, canine and bovine infections were determined. DIBI was strongly inhibitory to all isolates, displaying approximately 100-fold more inhibitory activity than deferiprone when compared on their molar iron-binding capacities. Sensitivity to DIBI was similar for both antibiotic-resistant and -sensitive isolates, including hospital- and community-acquired (United States 300) MRSA. DIBI inhibition was primarily bacteriostatic in nature at low concentration and was reversible by addition of Fe. DIBI also exhibited in vivo anti-infective activity in two distinct MRSA ATCC43300 infection and colonization models in mice. In a superficial skin wound infection model, topical application of DIBI provided a dose-dependent suppression of infection along with reduced wound inflammation. Intranasal DIBI reduced staphylococcal burden by >2 log in a MRSA nares carriage model. DIBI was also examined for its influence on antibiotic activities with a reference isolate ATCC6538, typically utilized to assess new antimicrobials. Sub-bacteriostatic concentrations of DIBI resulted in Fe-restricted growth and this physiological condition displayed increased sensitivity to GEN, CIP, and VAN. DIBI did not impair antibiotic activity but rather it enhanced overall killing. Importantly, recovery growth of survivors that typically followed an initial sub-MIC antibiotic killing phase was substantially suppressed by DIBI for each of the antibiotics examined. DIBI has promise for restricting staphylococcal infection on its own, regardless of the isolate’s animal source or antibiotic resistance profile. DIBI also has potential for use in combination with various classes of currently available antibiotics to improve their responses.